Deciphering the influence of NaCl on social behaviour of Bacillus subtilis - Murugan, Prem Anand; Sahu, Muktesh Kumar; Gupta, Manish Kumar; Sankar, T. Sabari; Chandran, Sivasurender; Matheshwaran, Saravanan (Royal Society open science, 2024)
Various environmental signals, such as temperature, pH, nutrient levels, salt content and the presence of other microorganisms, can influence biofilm’s development and dynamics. However, the innate mechanisms that govern at the molecular and cellular levels remain elusive. Here, we report the impact of physiologically relevant concentrations of NaCl on biofilm formation and the associated differences in an undomesticated natural isolate of Bacillus subtilis . NaCl exposure and its uptake by bacterial cells induced substantial changes in the architecture of pellicle biofilm and an upsurge in the expansion of biofilm colonies on agar surfaces. We have observed the upregulation of genes involved in motility and the downregulation of genes involved in the biosynthesis of extracellular matrix components through the transcription factor sigD, suggesting the possible underlying mechanisms. To further support these observations, we have used Δ sigD and Δ srfAC null mutants, which showed compromised NaCl-induced effects. Our results indicate that NaCl induces a lifestyle shift in B. subtilis from a sessile biofilm state to an independent unicellular motile state. Overall, we present evidence that NaCl can reprogramme gene expression and alter cellular morphology and the state of cells to adapt to motility, which facilitates the expansion of bacterial colonies.